2021
DOI: 10.13189/ujaf.2021.090407
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance's Policy on the Impact of Cash Holding in Indonesia

Abstract: The Asian Financial Crisis in 1997 and various other scandals in large companies in Indonesia led to the emergence of good corporate governance (GCG). Regulators on the capital markets understand that good corporate governance promotes transparency and improves the quality of financial reporting, including cash management, responsibly. Furthermore, high cash levels lead managers to misuse the fund for personal gain, because the assets under their supervision increase thereby. This research analyzes the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The practice of good corporate governance through the audit committee's function is expected to increase its focus on striving for a liquid firm financial condition [35]. In this case, the audit committee plays a role in assisting the board of commissioners in supervising the reporting process and company accounting policies to improve its financial performance [36,37].…”
Section: H3: Leverage Ratio Partially Has a Negative And Significant Effect On Firm Valuementioning
confidence: 99%
“…The practice of good corporate governance through the audit committee's function is expected to increase its focus on striving for a liquid firm financial condition [35]. In this case, the audit committee plays a role in assisting the board of commissioners in supervising the reporting process and company accounting policies to improve its financial performance [36,37].…”
Section: H3: Leverage Ratio Partially Has a Negative And Significant Effect On Firm Valuementioning
confidence: 99%
“…In this model, the dependent variable is CCH, proxied by CCH1 and CCH2. CCH1 is the proportion of cash and cash equivalents to total assets (Kusumawardani et al , 2021; Machokoto et al , 2021). Meanwhile, CCH2 is the proportion of cash and cash equivalents to total assets minus cash and cash equivalents (Bugshan et al , 2021; Nguyen et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Disclosing the company's energy policy (in general) , 1976). Another control variable was CASH, where cash holding plays an important role in the company's operational activities (Kusumawardani et al, 2021b;Hadjaat et al, 2021;Yudaruddin, 2019). Ortiz (2020) found that firms hold less cash when operating in a more transparent reporting environment.…”
Section: Methodsmentioning
confidence: 99%